2014
DOI: 10.1097/mib.0000000000000047
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Developing Purinergic Drugs for Gastrointestinal Diseases

Abstract: Treatments for IBD, IBS, FD or motility disorders are not adequate, and purinergic drugs offer exciting new possibilities. GI symptoms that could be targeted for therapy include visceral pain, inflammatory pain, dysmotility, constipation and diarrhea. The focus of this review is on potential for developing purinergic drugs for clinical trials to treat GI symptoms. Purinergic receptors are divided into adenosine P1 (A1,A2A,A2B,A3), ionotropic ATP-gated P2X ion channel (P2X1–7) or metabotropic P2Y1,2,4,6,11–14 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 225 publications
(264 reference statements)
1
47
0
1
Order By: Relevance
“…Our results provide new insights into how alterations in purine metabolism in response to tissue damage modulate the pathophysiology of IBD, that is, through interaction with the ILC3‐IL‐22 pathway. Given that drugs targeting the purinergic signaling for gastrointestinal diseases are being developed and accelerated toward testing in clinical trials,51, 52 our findings will help to clarify their therapeutic mechanisms.…”
Section: Discussionmentioning
confidence: 95%
“…Our results provide new insights into how alterations in purine metabolism in response to tissue damage modulate the pathophysiology of IBD, that is, through interaction with the ILC3‐IL‐22 pathway. Given that drugs targeting the purinergic signaling for gastrointestinal diseases are being developed and accelerated toward testing in clinical trials,51, 52 our findings will help to clarify their therapeutic mechanisms.…”
Section: Discussionmentioning
confidence: 95%
“…This assertion has been confirmed in many diseases, such as IBS and interstitial cystitis [6]. Clinical and fundamental research had found that a variety of analgesic drugs have good efficacy during the treatment of visceral pain, thus showing a broad therapeutic potential [7,8]. The application of purinergic receptor antagonists has also expanded the treatment of visceral pain.…”
Section: Introductionmentioning
confidence: 84%
“…Purinergic-based therapies may be useful to halt excessive inflammation and promote repair of neuroinflammatory disorders [4,80,123,124].…”
Section: Therapeutic Potentialmentioning
confidence: 99%